Pengaruh Kualitas Pelayanan terhadap Kepuasan Konsumen pada Gudang JNE Madukoro - Carolina Savitri Ajeng Margono; Rauly Sijabat; Shofif Sobaruddin Akbar (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
Service quality is a critical issue faced by service providers, as it plays a significant role in shaping customer satisfaction and maintaining customer trust for future services. A decline in service quality over time may negatively affect customers’ perceptions and loyalty. Therefore, this study aims to examine the effect of service quality dimensions on customer satisfaction. This research employed a quantitative approach using primary data collected through a survey method. The sampling technique used was probability sampling with a random sampling method, involving 98 customers as research respondents. Data were analyzed using SPSS version 24. The service quality dimensions analyzed in this study were Tangible, Reliability, Responsiveness, Assurance, and Empathy. The results of the analysis revealed that Tangible and Responsiveness did not have a significant effect on customer satisfaction. In contrast, Reliability, Assurance, and Empathy were found to have a significant positive influence on customer satisfaction. These findings indicate that customers place greater importance on service accuracy, employee competence, trustworthiness, and personal attention. Therefore, service providers are encouraged to prioritize improvements in Reliability, Assurance, and Empathy to enhance customer satisfaction and sustain long-term customer relationships.